Hybrid Membrane/PSA Processes for CO/N Separation - Isabel A.A.C. Esteves; José P.B. Mota (Adsorption Science & Technology)
New integrated schemes combining membrane permeation and pressure swing adsorption (PSA) have been developed for gas separation. By using the membrane as a pre-bulk separation unit and coupling it to the intrinsically dynamic periodic operation of the PSA, the separation performance of the hybrid scheme is enhanced with respect to that of the two stand-alone units. Instead of constant-composition regular feed, the PSA is fed with a mixture which is progressively enriched in the more adsorbed component during the pressurization and high-pressure adsorption steps of the cycle. This results in sharper concentration fronts. The hybrid scheme detailed here has been applied successfully to the bulk separation of an 30:70 mol% CO 2 /N 2 mixture over activated carbon. Process performance is reported in terms of product recovery and purity at cyclic steady state. Numerical simulations were validated by experimental work on a composite membrane and a laboratory-scale PSA unit. For the examples studied, product purity and recovery for the hybrid process were increased by 23% and 58% for CO 2 , and by 14% and 5% for N 2 , compared to an equivalent stand-alone PSA.